2021
DOI: 10.3390/ijms221910654
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of HDAC1 Enzymatic Activity after Stroke Protects Neurons from Ischemia/Reperfusion Damage and Attenuates Behavioral Deficits in Rats

Abstract: A therapeutic approach for promoting neuroprotection and brain functional regeneration after strokes is still lacking. Histone deacetylase 1 (HDAC1), which belongs to the histone deacetylase family, is involved in the transcriptional repression of cell-cycle-modulated genes and DNA damage repair during neurodegeneration. Our previous data showed that the protein level and enzymatic activity of HDAC1 are deregulated in stroke pathogenesis. A novel compound named 5104434 exhibits efficacy to selectively activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…29 Treatment with another synthetic activator of HDAC1 named 5104434 also reduces neuronal DNA DSB and rescues brain function in a rodent model of frontotemporal lobar degeneration and stroke. 71,76 Thus, HDAC1 activation provides a means of countering DNA damage and its deleterious effects on the brain in the aging and disease contexts.…”
Section: Hdac1 Ameliorates Oxidative Dna Damage and Protects Cognitiv...mentioning
confidence: 99%
See 1 more Smart Citation
“…29 Treatment with another synthetic activator of HDAC1 named 5104434 also reduces neuronal DNA DSB and rescues brain function in a rodent model of frontotemporal lobar degeneration and stroke. 71,76 Thus, HDAC1 activation provides a means of countering DNA damage and its deleterious effects on the brain in the aging and disease contexts.…”
Section: Hdac1 Ameliorates Oxidative Dna Damage and Protects Cognitiv...mentioning
confidence: 99%
“…Furthermore, pharmacological activation of HDAC1 by exifone stimulates OGG1 activity and reduces 8-oxoG oxidative lesions in the brain tissues of aged mice . Treatment with another synthetic activator of HDAC1 named 5104434 also reduces neuronal DNA DSB and rescues brain function in a rodent model of frontotemporal lobar degeneration and stroke. , Thus, HDAC1 activation provides a means of countering DNA damage and its deleterious effects on the brain in the aging and disease contexts.…”
Section: Modulations Of Hdac1 Activity To Stimulate Dna Repair and Im...mentioning
confidence: 99%
“…Previous studies have shown that the expression level and enzyme activity of HDAC1 decreased after stroke, and inhibition of HDAC1 promoted the infarct volume, neuronal loss, DNA damage, neuronal apoptosis, and levels of reactive oxygen species and inflammatory cytokines after stroke. 39 , 40 Moreover, HDAC1 is involved in regulating plaque formation in atherosclerotic mice. 41 Studies have shown that RUNX3 is also involved in regulating coronary atherosclerosis progression and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BCL11B and SATB2 expression positively correlated with neurological recovery rate suggesting their beneficial role in damage repair after ischemia. One of the possible explanation for their beneficial effect in brain ischemia is the ability to recruit components of NuRD chromatin remodeling complex, specifically HDAC1, since their activation is associated with the development of smaller ischemic lesions, improved neurological outcome and attenuated neuronal death 4 , 6 , 35 , 36 . Moreover, BCL11B expression had negative correlation with lesion volume, while SATB2 expression showed no correlation with detrimental factors, supporting their beneficial role in recovery after brain ischemia.…”
Section: Discussionmentioning
confidence: 99%